The awareness on Halal Food Products : a study among Diploma Students in UiTM Puncak Alam / Siti Nur Farina Sohaimi - Sohaimi, Siti Nur Farina (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Food is an essential element (dharuriyyah) to human being, as without food, humans can only survive for three days. Healthy and nutritious foods become the demand and dream of everybody regardless of demographic and geographic. Consuming a halal food becomes a must obligation obeyed by all Muslims around the world as it is an order from God (Allah). Nowadays, there is a dumping of food products in the market as a result of the import and export activities, the government’s open door policy, and the growth of the world food industry. This study attempts to examine the awareness on halal food products among diploma students in UiTM Puncak Alam. Furthermore, this research will shows the factors affecting the selection of food products among diploma students as well as the point of view of non-Muslim student towards halal food products. In order to get the data for analysis process, a set of questionnaires will be distributed to the students from two faculties, namely Academy of Contemporary Islamic Studies and Faculty of Health Science, which consists of two courses, namely Muamalat and Physiotherapy, respectively. The research suggested that the government should creating a special Halal Act on food-related matters to ensure and safeguard the interests of consumers, especially Muslims. The result of the study also suggested that every Muslim must ensure that every food taken should be from the source which is lawful and good as set by Allah SWT It is hope that the study can contribute to the empowerment of knowledge and the improvement in the practice of selecting healthy, nutritious and halal food among Muslims.